Morphometrical analysis of placental functional efficiency in normotensive versus preeclamptic South African black women. (2nd July 2016) - Maduray, K.; Moodley, J.; Naicker, T.
ABSTRACT: Objective : To assess the umbilical cord centrality, placental morphometrics, and functional efficiency in preeclampsia. Methods : Placental morphometry of normotensive ( n = 69) and preeclamptic ( n = 69) patients was evaluated. Results : There was a significant reduction in mean placental surface area ( p = 0.0001), length ( p = 0.0001), thickness ( p = 0.016), and volume ( p = 0.0001) in the preeclamptic than in the normotensive groups. Umbilical cord insertion was predominantly eccentric with marginal in early (29%) and late-onset preeclampsia (16%). Placental and birth weight was lower ( p = 0.0001) in preeclampsia than in the normotensive group. Placental efficiency was reduced in early-onset preeclampsia. Conclusion : This study demonstrates reduced placental morphometrics with impaired placental efficiency in preeclampsia.